Prevalence of secondary traumatic stress among social workers - Bride, Brian E. (2007)
Social workers are increasingly being called on to assist survivors of childhood abuse, domestic violence, violent crime, disasters, and war and terrorism. It has become increasingly apparent that the psychological effects of traumatic events extgend beyond those directly affected. Secondary traumatic stress (STS) is becoming viewed as an occupational hazard of providing direct services to traumatized populations. The purpose of the present study was to investigate the prevalence of STS in a sample of social workers by examining the frequency of individual symptoms; the frequency with which diagnostic criteria for posttraumatic stress disorder (PTSD) are met; and the severity of STS levels. Results indicate that social workers engaged in direct practice are highly likely to be secondarily exposed to traumatic events through their work with traumatized populations, many social workers are likely to experience at least some symptoms of STS, and a significant minority may beet the diagnostic criteria for PTSD. - Reproduced.
Keywords: Social workers